Pengelolaan Wakaf Uang untuk Pertanian (Studi Kasus Pada Global Wakaf Cabang Yogyakarta) - nurfazillah milawati; Nila Rahayu (Fakultas Ekonomi Islam Institut Agama Islam Nurul Hakim Kediri Lombok Barat, 2023)
With a very high flexibility, money waqf can be used as a source of funding to be invested or allocated to various types of programs for economic improvement of the public. One of the potential investment of money waqf is for the agricultural sector. In this case study, Global Waqf-ACT manages waqf funds into three divisions. The first division is fundraising which collects fund to be invested into productive business for agriculture to improve Indonesia's food security. Development of waqf funds was then carried out by LPM in order to increase the productivity of agricultural land by providing superior seeds, providing pest drugs, providing irrigation facilities and stabilizing the selling price of farmers' grain so as to improve the welfare of farmers in Jipang Village, Cepu District, Blora District, Central Java. Distribution of waqf in the form of distribution of rice for sale of Sodaqo Retail is based on buying and selling transactions with a certain amount, which is then distributed to the beneficiaries and for humanitarian aid in areas or countries suffering from disasters. To increase the amount of money waqf for agriculture for better agricultural productivity and prosperity of farmers in Jipang Village, Cepu District, Blora Regency, Central Java, the Global Waqf –ACT established a business capital loan program for farmers with a voluntary loan system. Keywords: Management, Money Waqf, Agriculture, Global Waqf